TINGKAT KEPUASAN PETANI TERHADAP PERAN LEMBAGA PERTANIAN DALAM MENDUKUNG KETAHANAN PANGAN - Pratiwi, Devi Arsinta; Nurdin, Fadilah; Megawati, Megawati; Astaman, Putra (Jurnal Riset Multidisiplin Agrisosco, 2025)
This study aims to: (1) determine the role/contribution of farmer groups in supporting food production in North Sinjai District, and (2) determine the level of farmer satisfaction with the role of farmer groups in achieving food security in North Sinjai District. This study used a quantitative descriptive approach. Data were obtained through questionnaires and in-depth interviews, using Importance Performance Analysis (IPA) and Consumer Satisfaction Index (CSI) analysis techniques. The IPA analysis results indicate that the performance of farmer groups exceeded farmers' expectations, with a conformity score of 114.8%. The CSI score of 71.34% indicates a high level of farmer satisfaction with the role of farmer groups. The results indicate that the role of farmer groups in North Sinjai District has been effective. This finding indicates that farmer groups not only meet but also exceed farmers' expectations in supporting food production and strengthening food security at the local level.